Dorsal Approach with Low-Profile Plate in Treatment of Scaphoid Nonunion with Proximal Pole Avascular Necrosis: A Case Report. Issue 3 (July 2021) - Zakhia-Douaihy, Ghassan; Issa, Mohamad; Naja, Ahmad Salaheddine
Abstract : Case: Avascular necrosis (AVN) and nonunion are common complications encountered with scaphoid waist fractures. We present a case of a 23-year-old man presenting with a right scaphoid fracture nonunion associated with AVN of the proximal pole. He was treated with a 1, 2 intercompartmental supraretinacular arterial bone graft (Zaidemberg technique) in combination with a dorsal plate yielding excellent functional and radiographic results. Conclusion: Scaphoid waist fracture nonunion with AVN of the proximal pole is challenging to treat and combining the Zaidemberg technique along with dorsal plating allows for easy access and excellent healing.